2014
DOI: 10.1039/c4cp03315a
|View full text |Cite
|
Sign up to set email alerts
|

A study on inorganic phase-change resist Ge2Sb2(1−x)Bi2xTe5and its mechanism

Abstract: The inorganic phase-change photoresist Ge2Sb1.5Bi0.5Te5 has a lot of advantages such as the two-sides of the photoresist, a large difference in the etching rate between it and Si, and so on, making it a promising candidate for use in the full-vacuum manufacture of the next generation ultra-large scale integrated circuits (ULSI). However, the physical origin of its excellent properties is still unclear, hindering its improvement and the optimization of its performance. In this work, we extended the Ge2Sb1.5Bi0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The exceptional piezo-, pyro-and ferroelectric properties of PVDF (polyvinylidene fluoride) and its most common copolymer P(VDF-TrFE) (poly[vinylidene fluoride-co-trifluoroethylene]) have stimulated numerous studies for many years that aimed at understanding its structural, morphological and electrical properties. [1][2][3][4][5][6] After application of a high electrical field, PVDF exhibits pyro 7,8 -and piezoelectric 9 properties. PVDF is a semicrystalline polymer consisting of linear chains with the sequence (CH 2 -CF 2 ), as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The exceptional piezo-, pyro-and ferroelectric properties of PVDF (polyvinylidene fluoride) and its most common copolymer P(VDF-TrFE) (poly[vinylidene fluoride-co-trifluoroethylene]) have stimulated numerous studies for many years that aimed at understanding its structural, morphological and electrical properties. [1][2][3][4][5][6] After application of a high electrical field, PVDF exhibits pyro 7,8 -and piezoelectric 9 properties. PVDF is a semicrystalline polymer consisting of linear chains with the sequence (CH 2 -CF 2 ), as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen production from pure water in the presence of visible light proceeded without degradation of the composite over time by using it in conjunction with the oxidation side photocatalyst. Prior to this study, most reported CdWO 4 synthesis methods involved hydrothermal synthesis [22][23][24] or solvothermal synthesis. 25 These methods entailed crystal formation to obtain CdWO 4 nanorods, nanobers, 22-24 and nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…XRD pasttern of PVDF indicated peaks at 2h 5 18.68 and 2h 5 21.58 arising out of reflections from (020) and (110) planes arising from aand the b-phase of PVDF, respectively [39,40]. There are two other peaks at 2h 5 26.68 arising out of reflections from (021) plane of the PVDF a phase and 2h 5 39.58 arising out due to the PVDF a phase [39,41,42]. The broad peak located at 228 composed of two peaks b phase PVDF (21.68) and a shoulder peak of PVDF with less intensity (JCPDS card no.…”
Section: Xrd Studiesmentioning
confidence: 99%